2010
DOI: 10.1186/1471-2458-10-322
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic influenza preparedness and health systems challenges in Asia: results from rapid analyses in 6 Asian countries

Abstract: BackgroundSince 2003, Asia-Pacific, particularly Southeast Asia, has received substantial attention because of the anticipation that it could be the epicentre of the next pandemic. There has been active investment but earlier review of pandemic preparedness plans in the region reveals that the translation of these strategic plans into operational plans is still lacking in some countries particularly those with low resources. The objective of this study is to understand the pandemic preparedness programmes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 14 publications
0
62
0
2
Order By: Relevance
“…Thus, improved distribution of resources has the potential to benefit public health outcomes beyond mitigation of pandemic influenza, and shortages or maldistribution may hinder control and mitigation efforts. But for public health to benefit effectively from improved distribution of resources, political, administrative and contextual hurdles may need to be overcome, including the mobilisation of resources across administrative boundaries [30]. Whilst drugs and ventilators may be readily re-distributed, other resources such as hospital beds and human resources may be more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, improved distribution of resources has the potential to benefit public health outcomes beyond mitigation of pandemic influenza, and shortages or maldistribution may hinder control and mitigation efforts. But for public health to benefit effectively from improved distribution of resources, political, administrative and contextual hurdles may need to be overcome, including the mobilisation of resources across administrative boundaries [30]. Whilst drugs and ventilators may be readily re-distributed, other resources such as hospital beds and human resources may be more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other contextual challenges for optimum distribution and utilisation of healthcare resources were identified in our previous qualitative analysis of pandemic preparedness programmes in relation to national health systems in our four GMS study countries (along with Indonesia and Taiwan) [30]. These include the need for: (i) greater emphasis on strategies for pandemic mitigation (since planning in the region was found to focus overwhelmingly on early detection and containment); (ii) translation of existing plans into operations, particularly at sub-national administrative levels; and, (iii) greater national ownership of preparedness activities, particularly in low resource countries where external funding is prominent, to ensure that the allocation of pandemic-related investments is aligned with national systems and priorities [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure appropriate use of antiviral drugs, a near-patient diagnostic test is therefore highly desirable (Barenfanger et al, 2000). In addition, there is a growing interest in deploying rapid detection methods in resource-limited settings (Ghosh and Vogt; Hanvoravongchai et al, 2010; Kubo et al, 2010; Ortiz et al, 2009; Oshitani, Kamigaki, and Suzuki, 2008) and expanding non-human influenza surveillance activities (e.g. (Antarasena et al, 2007; Samaan et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hanvoravongchai et al and the AsiaFluCap Project ( 15 ) reported results from rapid analyses of pandemic influenza preparedness in 6 Asian countries. Similar to the situation in Thailand, many of the countries were challenged by the need for greater flexibility in pandemic planning and implementation in order to accommodate changing transmission circumstances and different pandemic scenarios.…”
Section: Discussionmentioning
confidence: 99%